Contrastive Analysis of Adjectives of Quality of English and Fur Languages (British Journal of Multidisciplinary and Advanced Studies, 2023)
The research aims to compare and contrast adjectives of quality of English and Fur languages to find out the similarities and differences between them.  The researchers have adopted contrastive methodology to do this research. They compared and contrasted adjectives of quality of in English and Fur languages. The results of the research revealed that the two languages almost share the same adjectives of quality. English and Fur adjectives of quality modify the nouns. Moreover, the both languages use their adjectives of quality attributively and predicatively. The two languages use the intensifiers to strengthen the adjectives of quality. On the other hand, the both languages belong to different language families. English is from an Indo-European language family, whereas, Fur belongs to Nilo-Saharan language family. It is very obvious that English attributive adjectives go before the nouns which they describe whereas, Fur attributive use of adjectives (boorô, mandin , toy, dɨwwô, fattâ , dɨkkô ) come after the nouns which they modify. English predicative use of adjectives slightly differs from the Fur language, because in English language they come after the verb (be) however, in Fur language they go before the verb (ii=be). In addition to the position of intensifiers in Fur language differs from English ones. The English intensifiers go before the adjectives whereas; the Fur ones go after the adjectives. The differences in adjectives of quality between the two languages result in problems encountered by the Fur learners in learning English language and vice versa.